Optimization Of The Duration And Power Parameters Of Ultraviolet Radiation Treatment Of Sunflower Seeds (Texas Journal of Engineering and Technology, 2026)
This study investigated the optimal parameters of ultraviolet (UV) radiation treatment on sunflower (Helianthus annuus L.) seeds. Experiments were conducted on two varieties, Dilbar and Jahongir, to evaluate the effects of radiation intensity (30–90 W), distance (5–15 cm), and exposure time (10–20 minutes) on seed germination as well as seedling root and shoot length using a multi-factor experimental design. Second-order regression equations were developed, and corresponding 3D graphs were constructed. The results identified the optimal conditions for maximum efficiency: total lamp power of 60 W, distance of 10 cm, and exposure time of 15 minutes. The statistical adequacy of the models was confirmed using the Cochran, Student’s t, and Fisher criteria.